Síntese e caracterização de biopolímeros funcionalizados com APTES (3–aminopropiltrietoxisilano) para a adsorção de corante amarelo crepúsculo - Lima, Victor Veríssimo Cardoso (2019)
The biopolymers chitin (CTN) and chitosan (CTS) were functionalized with APTES (3–aminopropyltriethoxysilane) in order to enhance its adsorption potential for sunset yellow dye (SYD). The functionalization was evaluated by several techniques like FTIR (Fourier transform infrared spectroscopy), XRD (X–ray diffraction), N2 adsorption/desorption isotherms, SEM (scanning electron microscopy) and EDS (energy dispersive spectroscopy). The insertion of APTES in the biopolymers has improved the adsorption properties of both, CTN and CTS. The best performance was obtained using CTS functionalized with APTES (CTS–AP), at pH of 4.0, where, more than 99% of the SYD was removed from the solution. Adsorption of SYD on CTS–AP and CTS followed the n–order kinetic model, being that, the use of CTS–AP provided a much faster rate. Freundlich model has better described the isotherms of SYD adsorption on CTS–AP and CTS. An endothermic and physical adsorption was verified. The maximum adsorption capacities were 27 and 40 mg g–1 for CTS and CTS–AP, respectively. The functionalization of CTS with APTES was able to improve the adsorption capacity. However, the main role of the functionalization was provides a faster adsorption rate, decreasing in 50% the equilibrium time.